Late domain dependent E-cadherin recruitment into extracellular vesicles - Bänfer, Sebastian; Kutscher, Sophie; Fleck, Fenja; Dienst, Martina; Preußer, Christian; Pogge von Strandmann, Elke; Jacob, Ralf (Frontiers in Cell and Developmental Biology, 2022)
E-cadherin, a transmembrane protein involved in epithelial cell-cell adhesion and signaling, is found in exosomal fractions isolated from human body fluids. A cellular mechanism for recruitment of E-cadherin into extracellular vesicles (EVs) has not yet been defined. Here, we show that E-cadherin is incorporated into the membrane of EVs with the extracellular domain exposed at the vesicle surface. This recruitment depends on the endosomal sorting complex required for transport I (ESCRT-I) component Tsg101 and a highly conserved tetrapeptide P(S/T)AP late domain motif in the cytoplasmic tail of E-cadherin that mediates interaction with Tsg101. Mutation of this motif results in a loss of interaction and a dramatic decrease in exosomal E-cadherin secretion. We conclude, that the process of late domain mediated exosomal recruitment is exerted by this endogenous non-ESCRT transmembrane protein.